Making Research Matter : Steps to Impact for Health and Care Researchers - Lamont, Tara.; Project Muse. (Bristol : Policy Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence. Written by a leading expert in the field, this practical and accessible book is an essential guide to knowledge exchange, impact and research dissemination in health and social care.
Easy-read versions -- Choosing the right images -- 6 WHO you want to reach -- policymakers and managers -- Summary -- Who makes the decisions? -- Step one: ask the right questions -- Step two: understand the context -- How policymakers use evidence -- How healthcare managers use evidence -- Step three: involve the right people -- Step four: partner with organisations, networks and champions -- Step five: present content which is engaging and accessible -- Writing a policy brief -- 7 WHEN you could have most impact -- Summary -- It's all about timing -- What is the next hot topic?
Catching the moment.
Description based upon print version of record.
Description based on print version record.
Keywords: Public health -- Research; Public health -- Research; Electronic books